Kaygusuz Abdal's Mesnevi-i Baba Kaygusuz : critical edition and textual analysis - Oktay, Zeynep. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
The aim of this thesis is to bring to light an unpublished mesnevi of Kaygusuz Abdal and to introduce a new approach to the reading of his works. For the critical edition of Mesnevî-i Baba Kaygusuz, all of the manuscripts of the text have been examined and the three most correct manuscripts have been chosen for edition. The text has been edited in the transcription alphabet and the major variations among the three manuscripts have been given. All of the manuscripts have been described and the affinities between the three chosen manuscripts have been established. In the introduction to the analysis of the edited text, all of the historical sources on Kaygusuz Abdal have been studied and Kaygusuz Abdal’s life and works have been discussed. In the first part of the analysis, with the use of theoretical studies on mystical language, the text itself and other works of Kaygusuz Abdal , the concept of language in Mesnevî-i Baba Kaygusuz has been put forward. In Mesnevî-i Baba Kaygusuz, language creates meaning through the opposition of the apparent and the hidden. Its power of representation comes from the fact that it incorporates a duality which is the very form of theophany. This form is manifest in the text through the use of opposing symbol groups and different levels of meaning corresponding to different degrees of teaching. In the light of this concept of language, Kaygusuz Abdal’s use of the major symbols and doctrinal terms in Mesnevî-i Baba Kaygusuz has been studied. This study has revealed the structure of the text and Kaygusuz Abdal’s interpretation of the theory of vahdet-i vücud [unity of being] as expressed in Mesnevî-i Baba Kaygusuz. Kaygusuz Abdal’s interpretation of the theory of vahdet-i vücud includes a twofold manifestation of the divine being. In the first stage God manifests itself in a single being which is the batın (hidden) of all manifest being. In the second stage this being is manifest in the plurality of the apparent. The gnostic is the person capable of traveling from the apparent to the hidden until s/he reaches the most hidden, God itself.